2008
DOI: 10.1523/jneurosci.3248-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenergic Signaling in Infralimbic Cortex Increases Cell Excitability and Strengthens Memory for Fear Extinction

Abstract: Emotional arousal strengthens memory. This is most apparent in aversive conditioning, in which the stress-related neurotransmitter norepinephrine (NE) enhances associations between sensory stimuli and fear-inducing events. In contrast to conditioning, extinction decreases fear responses, and is thought to form a new memory. It is not known, however, whether NE is necessary for extinction learning. Previous work has shown that the infralimbic prefrontal cortex (IL) is a site of extinction consolidation. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
204
5
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 261 publications
(226 citation statements)
references
References 68 publications
(81 reference statements)
15
204
5
2
Order By: Relevance
“…In support of this hypothesis, it has been shown that EE increases the resilience of animals to social defeat stress by enhancing infralimbic cortical outputs to downstream limbic areas [9]. Also, in line with this possibility, it has been shown that an increased excitability in the PFC is associated with enhanced control over stress [33] and extinction learning [31]. Confirming our previous work [20,23,30], we also show in this study that EE reduces motor activity in the open field suggesting a faster habituation of enriched animals to novel environments (mild stress).…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…In support of this hypothesis, it has been shown that EE increases the resilience of animals to social defeat stress by enhancing infralimbic cortical outputs to downstream limbic areas [9]. Also, in line with this possibility, it has been shown that an increased excitability in the PFC is associated with enhanced control over stress [33] and extinction learning [31]. Confirming our previous work [20,23,30], we also show in this study that EE reduces motor activity in the open field suggesting a faster habituation of enriched animals to novel environments (mild stress).…”
Section: Discussionmentioning
confidence: 71%
“…This analysis also showed that foot shock stress (0.6 mA, 2 s) increased corticosterone concentrations in vehicle injected animals (Fig. 4B) although it did not reach statistical significance (F (1,31) =1.36; p= 0.25). Picrotoxin did not significantly change the stress-induced concentrations of corticosterone compared to vehicle (F (1,31) = 4.12; n.s.…”
Section: Effects Of Muscimol and Picrotoxin Microinjections Into Thementioning
confidence: 73%
See 2 more Smart Citations
“…However, this interpretation is unlikely given that b-AR activation enhances, rather than impedes, memory formation (McGaugh, 2000). Accordingly, b-AR blockade impairs, rather than facilitates, extinction of several appetitive and aversive behaviors (Merlo and Izquierdo, 1967;Mueller et al, 2008;LaLumiere et al, 2010).…”
Section: Discussionmentioning
confidence: 99%